MOVEMENT TRANSFORMATIONS IN ENGLISH SENTENCE CONSTRUCTION - Adha, Ruly (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2017)
Chomsky states that language is a mirror of the mind. From that opinion, he creates a concept which is known as competence and performance. Competence is the fluent native speaker’s knowledge of his language; meanwhile, performance is what people actually say or understand by what someone else says on a given situation. Chomsky adds that there are two structures involved in constructing a sentence namely, Deep Structure and Surface Structure. A sentence always derives from Deep Structure which exists in the mind of speakers. Then, syntactic rules will be applied to the Deep Structure. After applying the rules, Surface Structure will be obtained. The syntactic rules applied in a sentence are Movement Transformation, Deletion Transformation, and Substitution Transformation. However, the main discussion in this article is Movement Transformation. This article will elaborate some types of movement transformation in constructing English sentences.